FIGHT CORRUPTION AT THE STATE AND MUNICIPAL LEVELS IN RUSSIA:: FOLLOWING SOCIOLOGICAL (FIELD) RESEARCHES - A. Vorontsov, Sergey; Y. Mamychev, Alexey; V. Ponedelkov, Alexander; V. Kolesnik , Veronika; A. Boyko, Natalia (Revista Gênero e Interdisciplinaridade, 2021)
This paper presents the materials of sociological (field) research devoted to the problems of combating corruption at the state and municipal levels, as well as the analysis of data and expert opinions obtained in the course of field research. The sociological study was conducted in the form of a survey of experts in thirteen constituent entities of the Russian Federation, in which more than 1000 people were interviewed. On the basis of the data obtained, the authors substantiate the need for the adequacy and effectiveness of the fight against corruption in Russian society to strengthen the influence of ethical and moral norms on the observance of prohibitions, restrictions, and requirements established in order to combat corruption, as well as the development of additional mechanisms and tools for preventing corruption manifestations. At the same time, it is substantiated that the adopted anti-corruption norms require not only legalization, but also legitimation, that is, recognition and support by citizens and society of this work as a whole. The authors are convinced that the combination of these two components can increase the effectiveness of the prevention of corruption offenses in the Russian Federation. In addition, the work separately examines the anti-corruption legislative initiatives of political parties and social movements, their significance and role in the fight against corruption interaction in society.